Menerobos Badai Revolusi: Dinamika Pengangkatan Sampurno Kolopaking Menjadi Bupati Bekasi, 1951 (Jurnal Sejarah Indonesia, 2025)
This study examines the appointment of Sampurno Kolopaking as Regent of Bekasi in 1951, an important episode in local political history that has received limited attention in Indonesian historiography. Sampurno Kolopaking, previously Regent of Deli Serdang (1947–1951), was assigned to lead Bekasi during the post-revolutionary political transition, when the central government sought to consolidate administrative authority in newly reorganized territories. The appointment was not merely administrative but laden with political dimensions, involving competing interests of the central government, local elites, and national political parties. The study aims to investigate the political background behind Kolopaking’s appointment, emphasizing the dominant role of the Ministry of Home Affairs in determining local leadership. Using a local political history approach, it relies on primary sources including Dutch and Dutch East Indies newspaper archives, official government documents, and secondary academic literature. This method allows an in-depth analysis of the relationship between central policies and local responses. Findings indicate that Kolopaking’s appointment represented a strategy by the central government to ensure the loyalty of regional officials, while the aspirations of the Regional Administrative Council (Bestuurscollege van de kabupaten) were often overlooked. Interventions by national political parties, especially PNI and Masyumi, also influenced the selection process. This dynamic reflects the complexity of post-revolutionary politics, where central authority remained dominant, yet national political fragmentation limited space for local actors. The study not only fills a historiographical gap regarding Sampurno Kolopaking but also enhances understanding of center–regional relations, political party roles, and the consolidation of the Indonesian state during the early post-independence period.
Keywords: Bekasi; Central–Local Politics; Regent; Sampurno Kolopaking